A nano-granular CuS-NiS composite negative electrode material and its preparation method and application
Through a simple one-step method, nanoparticle CuS-NiS composite anode material is synthesized, which solves the problem of insufficient performance of copper-based compound anode material, and realizes a supercapacitor with high energy density and cycle stability, simplifies the preparation process and is applicable. 于多种能源存储设备。
Patent Information
- Application Number
- CN202311379297.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-24
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-10-24
AI Technical Summary
The capacity and rate performance of existing copper-based compound negative electrode materials are low, the preparation process is complex, it is difficult to produce on a large scale, and the matching ability with the positive electrode materials is insufficient, which limits the energy density and cycle stability of the supercapacitor.
A simple one-step method is used to synthesize nanoparticle CuS-NiS composite anode material, and use copper sheets, foamed copper and foamed nickel as copper sources and nickel sources through solvothermal reactions, and thiourea as sulfur sources to form three-dimensional layers. The nano-CuS-NiS composite with a granular convex structure avoids the use of metal salts and binders and simplifies the preparation process.
It achieves high area specific capacitance and rate performance. The assembled asymmetric supercapacitor has high energy density and excellent cycling stability. It is suitable for the next generation of high-performance supercapacitors and has application prospects in the fields of lithium-ion batteries and electrocatalytics.
Smart Images

Figure CN118280739B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of novel energy storage materials and nano material synthesis, and specifically relates to a nano granular CuS-NiS composite negative electrode material and a preparation method thereof and application in super capacitors. Background Art
[0002] Among energy storage devices, supercapacitors, lithium batteries, and fuel cells are the most critical competitors. Supercapacitors have the advantages of high power density, fast charging speed, long service life, safety, environmental protection, and good low-temperature performance. They are widely used in new energy buses and large lifting equipment. At present, the capacity of positive electrode materials has reached a very high level, while the research and capacity of negative electrode materials are relatively lagging behind. The mismatch between the positive and negative electrodes leads to little improvement in the energy density of assembled asymmetric supercapacitors. In recent years, widely studied carbon materials (such as activated carbon, carbon nanotubes, and graphene) are often used as negative electrode materials for supercapacitors due to their low theoretical specific capacitance (less than 300 F g -1 ), the matching problem of positive and negative electrodes is still prominent, which seriously restricts the widespread application of supercapacitors in the energy storage industry. Therefore, designing a new type of high-capacity negative electrode material with good matching with the positive electrode is the key to improving the energy density of supercapacitors.
[0003] Among different compounds, transition metal sulfides have multiple valence states and larger lattice spacing, which is conducive to the entry of electrolyte ions and ensures the smooth progress of redox reactions, thereby obtaining higher conductivity and specific capacitance. As a member of the metal sulfide family, CuS has attracted people's attention due to its abundant copper sources, low price, variable valence states and excellent electrochemical properties. Considering the electronegativity of CuS, Cu 2+ As an electron donor, S 2- As an electron acceptor, Cu 2+ To S 2- The improved electron transfer ability ultimately shows excellent electrochemical performance and has a wide range of applications in energy storage, electrocatalysts, etc. However, when used as a supercapacitor negative electrode material, the wider band gap hinders the excitation of carriers to the conduction band, resulting in a decrease in the material's electrical conductivity and poor electrochemical performance. In order to improve the electrochemical performance of nano CuS negative electrode materials, other elements are doped into them. For example, Han et al. used a hard template method to prepare Ta-Cu7S4 negative electrode materials. At 1Ag -1 The specific capacitance is 675F g -1 , at 10Ag -1 The capacitance retention rate is 53.8% when the assembled solid-state asymmetric supercapacitor (Ta-Cu7S4 / / NiCo hydroxide / Cu(OH)2 / CF) is 800Wkg-1 The energy density is 111.1Whkg -1 , and the cycle stability after 5000 cycles is 83.3% (Xuzhao Han, et al. Construction of Ta-Cu7S4 negative electrode for high-performance all-solidstate asymmetric supercapacitor[J]. Chemical Engineering Journal, 2021, 403:126471).
[0004] Since the content of another metal element introduced by doping is generally very small, the degree of improvement in the capacity of the electrode material is often limited. A nano-hybrid material system composed of two different metal compounds, that is, a composite of nano-metal compounds, is another effective method to improve the capacity of electrode materials. Metal compound composites can synergistically improve the inherent properties of each component, such as electron transfer / ion transport, capacity and cycle stability, so they have better electronic conductivity and richer redox reactions, thereby improving their electrochemical properties such as capacity. NiS is considered to be a promising supercapacitor electrode material due to its simple preparation, environmental friendliness and high capacity. It can be composited with other negative electrode materials to improve its electrochemical performance. For example, Wang et al. used electrodeposition and multi-step ion layer adsorption reaction to prepare MoS2 / NiS composite negative electrode materials on nickel foam. The electrolyte was 1.0M Na2SO4 at 1mA cm -2 The area specific capacitance is 0.72 F cm -2 (Hongyan Wang, et al. In situ growth MoS2 / NiS composites on Ni foamas electrode materials for supercapacitors[J]. Materials Today Communications, 2023, 34: 105041). Chinese invention patent CN113764196B, "A copper pentasulfide / iron oxide composite electrode material and its preparation method", discloses a microspherical Cu9S5 / Fe2O3 composite negative electrode material prepared by a one-step hydrothermal method, with a loading of 5 mg cm -2 , at 1A g -1 The calculated area specific capacitance is 7.52 F cm -2 , 5 times the rate is 42.9%. Zhang et al. synthesized Fe3O4@C / CuO / CF anode material on copper foam using a four-step method and achieved a high conductivity at 5 mA cm -2The area specific capacitance is 15 F cm -2 , at 25mA cm -2 The rate of the asymmetric supercapacitor assembled with the positive electrode material Ni-Co hydroxide / Cu(OH)2 is 47.3%, and the capacitance retention rate after 5000 cycles is 88%, while that of Fe3O4 / CuO / CF without carbon is only 3%. -1 The energy density is 90.6Wh kg -1 The capacitance retention rate after 5000 cycles was 86% (Dongbin Zhang, et al. Hierarchical carbon-decorated Fe3O4 on hollow CuOnanotube array: Fabrication and used as negative material for ultrahigh-energydensity hybrid supercapacitor[J]. Chemical Engineering Journal, 2018, 349: 491-499).
[0005] The construction of a composite of transition metal compounds forms a special electronic structure due to the special synergistic effect, heterojunction and internal electric field between the two active substances, which can improve the electrochemical properties of the supercapacitor negative electrode material, such as conductivity and capacity. At present, although the capacity of copper-based compounds has been improved to a certain extent, their area specific capacitance and rate are still relatively low, and the preparation process is complicated and not easy to mass produce. Therefore, it is a huge challenge in current energy storage devices to develop a preparation method with simple process, less chemical raw materials and low cost to synthesize a binder-free nano-CuS composite negative electrode material with many electroactive sites, high area specific capacitance and rate performance, and to assemble asymmetric supercapacitors with high energy density and outstanding cycle stability. Summary of the invention
[0006] In view of the outstanding problems of low capacity and rate performance and complex preparation process of existing copper-based compound negative electrode materials, the purpose of the present invention is to provide a simple one-step synthesis of granular CuS-NiS composite negative electrode materials. Due to the synergistic effect of multiple components, heterojunction and the generated internal electric field and the unique three-dimensional layered granular protrusion structure, it has excellent area specific capacitance and good rate performance. The assembled device has high energy density and outstanding cycle stability, and can be directly applied to the next generation of high-performance supercapacitors.
[0007] In order to realize the nano-granular CuS-NiS composite negative electrode material and the preparation method thereof of the present invention, the following preparation steps are included:
[0008] (1) Dissolve thiourea in anhydrous ethanol and deionized water, and obtain a uniform mixed solution after magnetic stirring.
[0009] (2) The mixed solution is transferred into a polytetrafluoroethylene liner, and three different pretreated metal sheets are added. After the reactor is sealed, a solvent thermal reaction is carried out in a forced air drying oven; after the reaction, the mixture is cooled to room temperature, and the mixture is washed and dried to obtain a copper sheet-loaded nano-CuS-NiS composite.
[0010] The concentration of thiourea in the mixed solution in step 1 is 30-50 mM.
[0011] The volume ratio of anhydrous ethanol to deionized water in the mixed solution in step 1 is 3:1.
[0012] In step 2, the area ratio of the nickel foam or nickel mesh and the copper foam or copper mesh to the copper sheet is 1:1:2.
[0013] The pretreatment process of the three different metal sheets in step 2 is to ultrasonically pickle the nickel foam or nickel mesh, the copper foam or copper mesh and the copper sheet in a 3M HCl solution for 10 to 15 minutes to remove surface oxides and impurities, and then ultrasonically clean them in deionized water for 3 to 5 times until the solution is neutral, and then clean them in anhydrous ethanol and dry them.
[0014] The temperature of the solvent thermal reaction in step 2 is 140-160° C., and the reaction time is 4-12 hours.
[0015] Compared with the prior art, the present invention has the following advantages:
[0016] (1) The present invention uses copper sheet, copper foam and nickel foam as copper source and nickel source respectively, thiourea as sulfur source, and a mixed solution of anhydrous ethanol and deionized water as solvent to synthesize a copper sheet-loaded nano-granular CuS-NiS composite by solvothermal reaction. The active material is firmly grown in situ on the conductive copper sheet, has good conductivity and structural stability, does not use metal salts, and avoids the use of adhesives and complex coating processes.
[0017] (2) In the present invention, in addition to the copper ions generated by the copper sheet itself, the foamed copper and foamed nickel have a large specific surface area under the etching of thiourea, and a large amount of copper ions and nickel ions enter the solution, diffuse to the vicinity of the copper sheet and combine with the sulfur ions to generate a nano CuS-NiS composite composed of a large amount of CuS and a small amount of NiS.
[0018] (3) The nano CuS-NiS composite of the present invention has a three-dimensional layered granular protrusion structure composed of a large number of mud-like nanoparticles and rock candy-like micron particles on the surface. The gaps between the particles and the pits on the surface have a specific surface area and abundant electroactive sites, which provide a strong structural guarantee for its high capacity and rate performance, and is expected to be widely used in electrode materials of supercapacitors and even other energy storage devices.
[0019] (4) Due to the introduction of NiS, the nano CuS-NiS composite of the present invention has a synergistic effect of multiple components, a nano heterojunction, and an internal electric field, which can significantly improve the conductivity of the material and the rapid transfer kinetics of electrons, allowing more electroactive materials to fully participate in the Faraday pseudocapacitive reaction.
[0020] (5) The preparation process of the copper sheet-loaded nanoparticle CuS-NiS composite of the present invention is simple, does not require metal salts, does not require complex equipment and devices, is green and environmentally friendly, and is convenient for industrial large-scale production. The composite negative electrode material has outstanding supercapacitor negative electrode performance at a current density of 5 mA cm -2 The area specific capacitance is as high as 23.27F cm -2 , at a high current density of 50mAcm -2 The capacitance retention rate is 81.7%; the assembled CuS-NiS / / NiCo2S4 asymmetric supercapacitor has an outstanding areal energy density of 1.4 mW h cm -2 After 20,000 cycles, the capacitance retention rate is as high as 428%, which has surprisingly high cycle stability. The prepared composite negative electrode material can be directly applied to the next generation of supercapacitors with high energy density, and also has certain application prospects in lithium-ion batteries and electrocatalysis. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the XRD spectrum of the copper sheet loaded nano-CuS-NiS composite prepared in Example 1.
[0022] Figure 2 These are scanning electron microscope (SEM) photos of the copper sheet loaded with nano-CuS-NiS composite prepared in Example 1 at different magnifications.
[0023] Figure 3 These are transmission electron microscope TEM and HTEM photos of the copper sheet loaded nano-CuS-NiS composite prepared in Example 1.
[0024] Figure 4 The electrochemical performance of the copper sheet-loaded nano-CuS-NiS composite prepared in Example 1 is (a) cyclic voltammetry curves at different scan rates, (b) constant current charge-discharge curves at different current densities, and (c) specific capacitance curves at different current densities.
[0025] Figure 5 The copper sheet loaded with nano CuS-NiS composite prepared in Examples 2 to 4 was subjected to a current density of 5 mA cm -2 Constant current charge and discharge curve.
[0026] Figure 6 The copper sheet loaded with nano copper-based composite prepared in Comparative Examples 1 to 3 was subjected to a current density of 50 mA cm -2 Constant current charge and discharge curve.
[0027] Figure 7 Electrochemical performance of the assembled ASC device (a) at a current density of 20 mA cm -2 (a) Constant current charge-discharge curves at different voltages, (b) Cyclic voltammetry curves at different scan rates, (c) Constant current charge-discharge curves at different current densities, (d) Area specific capacitance curves at different current densities, (e) Power density and energy density curves, (f) Cyclic stability curves for 20,000 cycles (g) Impedance spectra before and after cycling.
[0028] Figure 8 These are photos showing the brightness of a small LED bulb at different times after two ASC devices are connected in series. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer, the present invention is further described in detail below in conjunction with embodiments, comparative examples and accompanying drawings. It should be understood that the embodiments are only used to explain the present invention and are not used to limit the scope of the present invention.
[0030] Example 1
[0031] (1) Nickel foam (2.2 cm×3 cm), copper foam (2.2 cm×3 cm) and copper sheet (2.2 cm×6 cm) were ultrasonically cleaned in a 3M HCl solution for 15 min to remove surface oxides and impurities, and then ultrasonically cleaned in deionized water for 3 to 5 times until the solution was neutral, and then cleaned in anhydrous ethanol and dried in a forced air drying oven at 60° C. for 50 min to obtain pretreated nickel foam, copper foam and copper sheet;
[0032] (2) 0.246 g of thiourea was added to a mixed solution of 60 mL of anhydrous ethanol and 20 mL of deionized water, and a uniform solution was formed after magnetic stirring for 30 min;
[0033] (3) The uniform solution was transferred into a polytetrafluoroethylene liner, and three pretreated metal sheets, foam nickel, foam copper and copper sheet, were added. The reactor was sealed and placed in a drying oven at 150°C for 8 hours. After cooling to room temperature, the copper sheet with active material grown was taken out, washed several times with deionized water and anhydrous ethanol, and dried at 60°C for 10 hours to obtain the copper sheet loaded with nano-CuS-NiS composite negative electrode material.
[0034] The phase and structure of the negative electrode material prepared in Example 1 were characterized by X-ray diffractometer (XRD), and the diffraction angle (2θ) ranged from 10° to 80°. Figure 1 The XRD spectrum of nano CuS-NiS loaded on copper sheet, at 43.41°, 50.56° and 74.3°, corresponds to the crystal planes (111), (200) and (220) of the copper sheet. The diffraction peaks at 43.7° and 48° correspond to the (115) and (200) crystal planes of CuS, and its standard card is PDF#78-2122; the diffraction peak at 45.23° corresponds to the (102) crystal plane of NiS, and its standard card is PDF#89-1956. This result shows that the prepared negative electrode material is a copper sheet loaded CuS-NiS composite in which two sulfides of CuS and NiS coexist. In addition, there are no other diffraction peaks in the spectrum, indicating that there are no other impurities in the product.
[0035] The SEM photo of the copper sheet loaded with nano CuS-NiS composite negative electrode material prepared in Example 1 is as follows Figure 2 As shown. As can be seen from Figure (a), there are some irregularly shaped, raised rock candy-like particles evenly distributed on the surface of the material, with a length of 10 to 30um. These particles grow firmly on the copper substrate. The micron particles in Figure (b) are polyhedrons with regular pyramid-like structures, and there are some corrosion-like pits around them. These raised rock candy-like particles and pits have a larger specific surface area and more active sites. As can be seen from the photo in Figure (c), the material is composed of a large number of uniform nanoparticles connected together. Further enlarged photos in Figure (d) clearly show that these nanoparticles are in a mud-like structure, with a size of 80 to 500nm, a rough particle surface, and a large number of gaps between particles, with a width of 10 to 50nm. It can be seen that the prepared copper sheet-loaded nano-CuS-NiS composite is a three-dimensional layered granular protrusion structure composed of a large number of mud-like nanoparticles and their rock candy-like micron particles. They grow firmly on the copper sheet. A large number of nanoparticles with rough surfaces, protruding rock candy-like micron particles and some pits on the surface have a large specific surface area and can provide more electroactive sites. The large number of gaps between the micron particles are not only conducive to the full contact between the electrolyte and the electroactive material during the electrochemical reaction, but also conducive to the rapid diffusion and transfer of the electrolyte ions, so that more active materials can fully participate in the Faraday reaction. This structure is very beneficial to its electrochemical performance.
[0036] Figure 3 TEM photo of the nano CuS-NiS composite prepared in Example 1. Figure 3 (a) It can be seen that the material is composed of a large number of soil-like particles connected to each other. Surprisingly, a very thin amorphous layer is evenly coated on the surface of the particles, with a thickness of about 20nm (the thin line in the figure). The existence of the amorphous layer indicates that there are a large number of lattice defects on the surface of the nanoparticles, which is very beneficial to their electrochemical properties. Figure 3 (b) is a high-resolution HTEM image. The lattice spacing is 0.20nm and 0.21nm, which correspond to the (102) and (115) crystal planes of NiS and CuS in the composite, respectively. This further proves that the two sulfides, CuS and NiS, coexist in the product, and the prepared material is a CuS-NiS composite with a large number of heterogeneous structures between the grains. The two sulfides in the composite produce a synergistic effect during the electrochemical reaction, and the heterojunction can significantly increase the electron transfer rate in the material, thereby significantly increasing the capacity of the electrode material.
[0037] The prepared copper sheet loaded nanoparticle CuS-NiS composite negative electrode material was used as the working electrode, platinum wire as the counter electrode, Ag / AgCl electrode as the reference electrode, and 6 mol L -1 The KOH aqueous solution was used as the electrolyte. The electrochemical performance test was carried out in the three-electrode system. The test included cyclic voltammetry curve and constant current charge-discharge curve. The potential window of the cyclic voltammetry test was -1.2~0.2V, and the current density of the constant current charge-discharge test was 5~70mAcm -2 .
[0038] The electrochemical performance test results of the prepared copper sheet loaded nanoparticle CuS-NiS composite negative electrode material are shown in Figure 4 . Figure 4 (a) Cyclic voltammetry curves at different scan rates. Each curve has an obvious redox peak, indicating that a Faradaic pseudocapacitive reaction occurs. Figure 4 (b) is the constant current charge-discharge curve under different current densities. Each curve has an obvious potential platform, which further proves that the electrode material undergoes a pseudocapacitive reaction, which is consistent with the CV test results. Figure 4 (c) is the area specific capacitance curve under different current densities. When the current density is 5, 10, 20, 30 and 50 mA cm -2 The area specific capacitances are 23.27, 22.4, 20.72, 19.55 and 19.00 F cm -2 , at a high current density of 50 mA cm -2The capacitance retention rate is 81.7%. It can be seen that the prepared copper sheet loaded nano-particle CuS-NiS composite negative electrode material has outstanding area specific capacitance and excellent rate performance, and can be directly applied to the negative electrode material of the next generation of high-performance supercapacitors.
[0039] Example 2
[0040] The difference between Example 2 and Example 1 is that in step (3), the reaction is carried out in a drying oven at 150°C for 4 hours. The other preparation conditions and processes are the same as those in Example 1, and a copper sheet-loaded nano CuS-NiS composite negative electrode material is obtained. Figure 5 The curve shows that the electrode is -2 The area specific capacitance is 7.23 F cm -2 .
[0041] Example 3
[0042] The difference between Example 3 and Example 1 is that in step (3), the reaction is carried out in a drying oven at 150°C for 6 hours, and the other preparation conditions and processes are the same as those in Example 1. A copper sheet loaded with nano CuS-NiS composite negative electrode material is obtained. Figure 5 The curve shows that the electrode is -2 The area specific capacitance is 5.88 F cm -2 .
[0043] Example 4
[0044] The difference between Example 4 and Example 1 is that in step (3), the reaction is carried out in a drying oven at 150°C for 10 hours. The other preparation conditions and processes are the same as those in Example 1, and a copper sheet-loaded nano CuS-NiS composite negative electrode material is obtained. Figure 5 The curve shows that the electrode is -2 The area specific capacitance is 13.37 F cm -2 .
[0045] Comparative Example 1
[0046] The difference between Comparative Example 1 and Example 1 is that in step (3), a pretreated copper sheet is added, and the other preparation conditions and processes are the same as those in Example 1 to obtain a copper sheet loaded with nano CuS negative electrode material. Figure 6 From the curve (a), it can be seen that the electrode is -2 The area specific capacitance is 3.83 F cm -2 .
[0047] Comparative Example 2
[0048] The difference between Comparative Example 2 and Example 1 is that in step (3), two metal sheets, pretreated nickel foam and copper sheet, are added, and the other preparation conditions and processes are the same as those in Example 1 to obtain a copper sheet-loaded nano CuS-NiS composite electrode material. Figure 6 From the curve (b), it can be seen that the electrode has a -2 The area specific capacitance is 1.93 F cm -2 .
[0049] Comparative Example 3
[0050] The difference between Comparative Example 3 and Example 1 is that in step (3), two metal sheets, pretreated foam copper and copper sheet, are added, and the other preparation conditions and processes are the same as those in Example 1 to obtain a copper sheet loaded nano CuS-NiS electrode material. Figure 6 From the curve (c), it can be seen that the electrode is -2 When the area specific capacitance is 2.10F cm -2 .
[0051] Example 5
[0052] (1) With nickel foam as the matrix, 0.946g of cobalt nitrate (Co(NO3)2·6H2O), 0.475g of nickel nitrate (Ni(NO3)2·6H2O), 0.185g of ammonium fluoride and 0.582g of urea were dissolved in 80mL of deionized water and stirred magnetically for 30min until completely dissolved to form a Ni-Co precursor solution. The solution and nickel foam were transferred into a polytetrafluoroethylene reactor and sealed, and reacted in a drying oven at 110℃ for 10h. After cooling to room temperature, the sample was taken out, washed with deionized water and anhydrous ethanol several times in sequence, and dried in a drying oven at 60℃ for 10h to obtain a nickel foam loaded Ni-Co precursor.
[0053] (2) 1.372 g of Na2S·9H2O was added to 80 mL of deionized water and magnetically stirred to form a uniform solution. The solution was then transferred to a polytetrafluoroethylene reactor and the above-mentioned nickel foam-loaded Ni-Co precursor was added. After sealing, the reaction was carried out at 90°C in a drying oven for 8 h. The reaction was then washed with deionized water and anhydrous ethanol in turn and dried in a drying oven at 60°C for 10 h to obtain a nickel foam-loaded NiCo2S4 nanowire array positive electrode material.
[0054] Assembling CuS-NiS / / NiCo2S4 asymmetric supercapacitors
[0055] In an asymmetric supercapacitor (ASC device), the prepared copper sheet-loaded nanoparticle CuS-NiS composite was used as the negative electrode material, and the nickel foam-loaded NiCo2S4 nanowires were used as the positive electrode material. -1KOH aqueous solution was used as the electrolyte, and the positive electrode and the negative electrode were assembled together in a beaker to obtain an asymmetric supercapacitor.
[0056] The electrochemical performance of the assembled ASC device was tested in a 6 M KOH aqueous solution using a two-electrode system. The CV curves were obtained at different scan rates of 5–70 mV s -1 The GCD curves are in the voltage window of 0-1.6V and different current densities of 5-70mAcm -2 The EIS test was conducted at a frequency range of 0.01-100kHz and an applied amplitude of 5mV. The cycling stability of the device was tested using the Blue Battery Test System at a current density of 50mA cm -2 The constant current charge and discharge cycle was tested for 20,000 times.
[0057] Electrochemical performance of the assembled CuS-NiS / / NiCo2S4 ASC device
[0058] In order to investigate the capacity and energy density of the prepared positive and negative electrode nanoelectrode materials, the electrochemical performance of the assembled CuS-NiS / / NiCo2S4ASC asymmetric supercapacitor was tested. Figure 7 (a) is the GCD curve of the device in different potential windows. No obvious polarization phenomenon occurs when the voltage window is gradually widened from 1.3 V to 1.7 V. In order to ensure the stable operation of the device, the working voltage of the test is selected to be 1.6 V. Figure 7 (b) is the CV curve of the device at different scan rates. As the scan rate increases, the curve shape remains basically unchanged, and no obvious polarization phenomenon occurs, indicating that the electron conduction and ion transfer rates in the device are fast, and it has excellent reversibility and capacitance. Figure 7 (c) is the GCD curve of the device at different current densities. The curves all have obvious potential platforms, indicating that a pseudocapacitive reaction occurs, which is consistent with the CV curve results. In addition, as the current density increases, the symmetry of the material becomes better, indicating that a larger current density is conducive to the oxidation reaction of sulfides and has a high Coulomb efficiency. Figure 7 (d) is the specific capacitance curve of the device at different current densities. -2 The area specific capacitances are 3.93 and 3.09 F cm -2 , with a good magnification of 78.6%. Energy density and power density are two key parameters for evaluating the application potential of energy storage devices. Figure 7 (e) shows that the assembled device has a power density of 4 mW cm -2 The energy density is as high as 1.4 mW h cm -2 When the power density is 40 mW cm -2Its energy density also remains high at 1.1 mW h cm -2 These results are much higher than those of ASCs devices assembled with transition metal-based anode materials in other literatures. Figure 7 (f) shows the assembled device at a high current density of 50 mA cm -2 The following is a cycle stability curve after 20,000 cycles. In the initial 10,000 cycles, the capacitance retention rate gradually increases. This is due to the gradual activation of the electrochemical active sites inside the material. After 20,000 cycles, the capacitance maintains 428% of the initial capacitance and the Coulomb efficiency remains 100%. Figure 7 (g) is the EIS spectrum of the device before and after 20,000 cycles. The arcs of their curves in the high-frequency region are small, indicating that the device's electron transfer impedance R ct The intercept of the spectrum after the cycle on the horizontal axis in the high-frequency region is smaller than that before the cycle, and the slope in the low-frequency region is significantly larger, indicating that it has a smaller series impedance R s and smaller electrolyte ion diffusion resistance. This indicates that the transfer impedance R ct Both the series impedance and the ion transfer impedance are significantly reduced after 20,000 cycles, which is consistent with its surprisingly high cycling stability.
[0059] In order to investigate the practical application value of the assembled CuS-NiS / / NiCo2S4ASC device, Figure 8 Connecting two devices in series can light up a red LED lamp for up to 110 minutes, which further confirms that the prepared copper sheet-loaded nano-CuS-NiS composite negative electrode material has great application potential in supercapacitors.
[0060] The prepared copper sheet loaded nanoparticle CuS-NiS composite negative electrode material has a current density of 5 mA cm -2 The area specific capacitance is as high as 23.27F cm -2 , at 50mAcm -2 19.00F cm -2 , the capacitance retention rate is 81.7%, and at a current density of 50 mA cm -2 The area specific capacitance of the assembled asymmetric supercapacitor is much higher than that of Comparative Examples 1, 2 and 3; the power density of the assembled asymmetric supercapacitor is 4.0 mW cm -2 The energy density is as high as 1.4 mWh cm -2 , the capacitance retention rate after 20,000 long-term cycles is as high as 428%, and the coulombic efficiency is 100%. The nanocomposite negative electrode materials prepared in Examples 2 to 4 also have high capacity, and they all have great application potential as the next generation of high-performance supercapacitor negative electrode materials.
[0061] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. For ordinary technicians in this field, other different forms of changes or modifications can be made based on the above descriptions and ideas. It is not necessary and impossible to list all the implementation methods here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a nano-granular CuS-NiS composite negative electrode material, characterized in that: The preparation comprises the following steps: (1) adding thiourea to a mixed solution of anhydrous ethanol and deionized water, and forming a uniform solution after magnetic stirring; (2) The uniform solution was transferred into a polytetrafluoroethylene liner, and three different pretreated metal sheets were added. The reactor was sealed and placed in a drying oven for solvothermal reaction. After cooling to room temperature, the copper sheet with active material grown was taken out, washed with deionized water and anhydrous ethanol several times, and dried in a drying oven at 60° C. for 10 h to obtain a copper sheet-loaded nanoparticle CuS-NiS composite negative electrode material; In step (1), the concentration of thiourea in the mixed solution is 30-50 mM; In step (1), the volume ratio of anhydrous ethanol to deionized water in the mixed solution is 3:1; In step (2), the three different metal sheets are nickel foam or nickel mesh, copper foam or copper mesh and copper sheet; In step (2), the area ratio of the three different metal sheets, nickel foam or nickel mesh, copper foam or copper mesh and copper sheet, is 1:1:2; In step (2), the temperature of the solvent thermal reaction is 140 to 160° C., and the reaction time is 4 to 12 hours; In step (2), the nano-granular CuS-NiS composite negative electrode material is a three-dimensional layered granular protrusion structure composed of a large number of nano- and micron-particles.
2. The preparation method according to claim 1, characterized in that: The pretreatment process of the three different metal sheets in step (2) is to ultrasonically pickle the nickel foam or nickel mesh, the copper foam or copper mesh and the copper sheet in a 3M HCl solution to remove surface oxides and impurities, and then ultrasonically clean them in deionized water for 3 to 5 times until the solution is neutral, and then clean them in anhydrous ethanol and dry them.
3. A nano-granular CuS-NiS composite negative electrode material is synthesized by the preparation method according to any one of claims 1 to 2, characterized in that: A copper sheet-loaded granular CuS-NiS composite was synthesized by solvothermal reaction using three different metal sheets as copper source and nickel source, thiourea as sulfur source, and a mixed solution of anhydrous ethanol and deionized water as solvent. The composite is a three-dimensional layered granular protrusion structure composed of a large number of nano- and micron-particles. No metal salts and binders are used in the preparation process, thus avoiding complex coating processes.
4. The use of a nano-granular CuS-NiS composite negative electrode material synthesized by the preparation method according to any one of claims 1 to 2, characterized in that: The copper sheet-loaded nano-granular CuS-NiS composite negative electrode material and the nickel foam-loaded NiCo2S4 positive electrode material are assembled into a CuS-NiS / / NiCo2S4 asymmetric supercapacitor, which can be directly applied to the next generation of high-performance supercapacitors and also has certain application prospects in the fields of lithium-ion batteries and electrocatalysis.
Citation Information
Patent Citations
A copper pentasulfide / iron oxide composite electrode material and its preparation method
CN113764196B
Method for preparing supercapacitor electrode material
CN108899222A
Preparation method and application of hollow cubic Ni3S4 / CuS2 supercapacitor electrode material
CN110950391A
Electrode material with core-shell structure constructed by taking foamed nickel as substrate
CN115188609A
Three-dimensional copper-nickel alloy electrode and preparation method and application thereof
CN116062841A
